Scope on triglyceride levels in elderly patients with dementia versus controls: a systematic review and meta-analysis - Ramadan, Heba (Nepal Journal of Neuroscience, 2024)
Introduction: Triglyceride levels vary among elderly patients with dementia. In this study, triglyceride levels were examined to demonstrate whether they increase or decrease in elderly dementia patients and other elderly individuals, whether there is a difference between elderly individuals with different forms of dementia and controls, and whether that difference is considered significant.Methods and materials: This analysis was performed via searching in Scopus, Web of Science, and Pubmed. A PRISMA checklist was followed to conduct the systematic review. The quality assessment was assessed by the Newcastle-Ottawa for case-control studies. Meta-analysis was performed by SPSS, Version 28.Results: Twenty-five studies consisting of 18943 cases and 212144 controls were included in the final analysis. Eighteen studies showed that the triglyceride levels in both patients and controls did not exceed the normal range (1.7 mmol/L or 150 mg/dl). A meta-analysis was also performed for the seven studies that revealed that triglyceride levels exceeded the normal range and no significant difference was found between the cases and controls (p-value =0.18, 95% CI).Conclusion: Triglyceride levels may not be a serious factor that should be considered in dementia, which differs from other areas of medicine, such as cardiovascular diseases.